Tibet seen as ideal stargazing spot. (December 2021) - Xin, Ling
Abstract : Chinese astronomers think that a location on Saishiteng Mountain in the Tibetan Plateau rivals existing astronomy meccas and could be home to next-generation observatories. Ling Xin reports.